Risk factors for postoperative venous thromboembolism in patients with lung cancer: a systematic review and meta-analysis - Fu, Jie; Zhou, Yiyi; Zhang, Feng; Lv, Ru; Hu, Lu; Zhang, Haiyan (Frontiers in Medicine, 2026)
ObjectiveVenous thromboembolism (VTE) is a serious complication following lung cancer surgery, which not only complicates treatment but may also delay cancer-specific therapies and even threaten patient survival. Currently, the risk factors for postoperative VTE in lung cancer patients remain unclear. Therefore, we conducted a meta-analysis to identify risk factors associated with VTE in these patients after surgery.MethodsWe systematically searched PubMed, Embase, Web of Science, Cochrane Library, China National Knowledge Infrastructure (CNKI), Wanfang Database, Chinese Biomedical Literature Database (CBM), and VIP Database for studies investigating risk factors for VTE after lung cancer surgery. The search covered the period from database inception to February 2025. Two reviewers independently screened the literature based on the inclusion and exclusion criteria, extracted data, and assessed the risk of bias in the included studies. Meta-analysis was performed using RevMan 5.4 software.ResultsA total of 21 studies involving 41,780 participants were included. The meta-analysis identified the following significant risk factors for VTE after lung cancer surgery: age ≥ 65 years old, hyperlipidemia, tumor staging III–IV, thoracotomy, operation time ≥ 2 h, intraoperative blood loss ≥ 200 mL, abnormal D-dimer levels, and preoperative chemotherapy. In contrast, no statistically significant associations were found between VTE occurrence and sex, age ≥ 60 years, smoking history, drinking history, body mass index ≥ 25 kg/m2, hypertension, coronary heart disease, diabetes, pathological type, operation time ≥ 3 h, tumor location, or type of lung resection.ConclusionThis meta-analysis confirmed that age ≥ 65 years, hyperlipidemia, advanced tumor stage (III–IV), thoracotomy, prolonged operation time (≥ 2 h), significant intraoperative blood loss (≥ 200 mL), abnormal D-dimer, and preoperative chemotherapy were risk factors for VTE in lung cancer patients after surgery. Targeted preventive measures based on these factors may help improve clinical outcomes in this patient population.